The Role of Electronics Human Resource Management (e-HRM) - Fransiska; Ayu Wulandari; Khuzaini; Syahrial Shaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The development of digital technology has brought significant changes to human resource management functions. The concept of Electronics Human Resource Management (e-HRM) enables organizations to manage HR functions more efficiently, flexibly, and in an integrated manner with digital technology that supports the Industry 4.0 revolution. Furthermore, the integration of e-HRM is expected to address the demands of Society 5.0, where technology is used to sustainably enhance human well-being. This article aims to examine the role of e-HRM in supporting organizational transformation toward Industry 4.0 and Society 5.0 through a conceptual study approach. The discussion results are expected to contribute to practitioners and researchers in developing an adaptive e-HRM implementation framework in the digital era.